INCORRECT SPEECH IMPACT: TEXT AND МETATEXT (Филолошки студии, 2021)
The article analyzes the interview given by the political consultant G. Pavlovsky to I. Shikhman, which is a kind of a metatext of manipulating public opinion. The manipulation model for the manipulator assumes that the addressee becomes an instrument to achieve a goal, for the addressee himself the manipulator is an equal participant in communication. Therefore, the concept of a point of view should be introduced into the description of manipulation, since only if the points of view on a communicative act do not coincide, the manipulator can achieve success. The 1999 situation that Pavlovsky describes – forming a new leader and ensuring electoral success – is possible with certain qualities of society, which the speaker characterizes as “weakness”. The structure of this situation may be described as follows: the sender is the speaker, the addressee, the customer, the object is a new leader, the model is an intelligent security officer, the tool is the media, the goal is to elect a new leader.